A Model Webquest for the Subject Panorama of English-Speaking Countries - Koke Camara, Youssouf (My University, 2012)
Nowadays ICTs, especially Computer Assisted Learning (CAL) materials, are given great importance as tools to support the teaching and learning process in higher education. The implementation of this technology is supported by the more progressive pedagogical approaches which promote the ideology of active learning and students’ self-assessment as better ways to construct new knowledge. The general aim of this diploma paper is to propose a model webquest to improve the teaching and learning process of the culture of English-speaking to students of the course English Language with a Second Foreign Language (French) at UCLV. Key Words: ICTs; multiple intelligence; task-based approach; webquest; English-speaking countries; culture; education.
Keywords: Literatura Inglesa/Estudio y Enseñanza; Multiple Intelligence; Computer Assisted Learning; Self Assessment